Rot : the bravest in the world! - Clanton, Ben, 1988- (Atheneum Books for Young Readers, 2020)
Rot the mutant potato must find a way to face his fear after his big brother, Snot, tells him there may be a dangerous Squirm in the magnificent mud pit he found.